A construção de identidades muçulmanas no Brasil: um estudo das comunidades sunitas da cidade de Campinas e do bairro paulistano do Brás - Castro, Cristina Maria de (2007)
This thesis analyses the construction of Muslim identities in Brasil, basically through the participant observation technique in the Islamic Center of Campinas and the Islamic Youth League, in Brás neighbourhood, in São Paulo city. I try to understand how this process of construction of identity happens towards: 1) the negotiation with the Brazilian host society, caracterized by the strong presence of Catholicism, the growth of Protestantism, a secular state, a basically Western culture, dependency on the USA and the Brazilian tradition of absorbing immigrants in a very strong process of assimmilation; 2) the globalization of islamite trends, also meaning the creation of a new consciousness of Ummah and; 3) the negotiations inside the Muslim communities, between Arabs and converts and also between men and women to define what means to be a male and female Muslim in Brazil. Finally, the comparative study of two Muslim communities with such different profiles as the Sunni communities of Campinas and Brás, allows to analyse until what point different occupations, ethnic backgrounds and spatial distributions promote the arising of different Islamic practices and speeches, towards the fields previously delimited .